Pengaruh Komisaris Independen , Dewan Direksi Dan Komite Audit Terhadap Manajemen Pajak (Studi Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode 2016 – 2020) - Maria Yovita Bete (Bulletin of Management and Business, 2022)
The Influence of Independent Commissioners, Board of Directors and Audit Committee on Tax Management (Empirical study on manufacturing companies in the consumer goods industry listed on the Indonesian Stock Exchange for the period 2016 – 2020). This study aims to determine the effect of independent commissioners, boards of directors and audit committees on tax management either partially or simultaneously. The research strategy used in this study is a causality research strategy with the research method used is the documentation method. which is quantitative in nature taken from the financial statements of manufacturing companies in the consumer goods industry sector that have been audited in 2016-2020 using the Software Eviews version 25 program. The results of the study prove that: 1) Independent Commissioners have a positive effect on tax management. 2) the board of directors has a negative effect on tax management. 3) the audit committee has a positive effect on tax management and 4) independent commissioners, the board of directors and the audit committee have a simultaneous effect on tax management.